The value of p (p^2 + p +1) if p =-1
2 answers:
Hey there!
p(p^2 + p + 1)
= -1(-1^2 + (-1) + 1)
= -1(-1^2 - 2 + 1)
= -1(-1^2) - 1(-2) - 1(1)
= 1 + 2 - 1
= 3 - 1
= 2
Therefore, your answer should be: 2
Good luck on your assignment and enjoy your day!
~Amphitrite1040:)
Answer:
The answer is 1
Step-by-step explanation:
p² + p + 1; p = -1
Now, Put p = - 1
p² + p + 1
(-1)² + (-1) + 1
1 - 1 + 1 = 1
Thus, The answer is 1
<u>-TheUnknownScientist</u><u> 72</u>
You might be interested in
The correct answer is d. Please give me brainlest I hope this helps let me know if it’s correct or not okay
<span>300.0109
I hope this helps
300=3 hundreds
.0109= 109 hundredths</span>
Answer:
V=lwh
/3
Step-by-step explanation:
The correct answer is:
$5.75
2.3% of 250 is 5.75.
For the first one it might be 26? i’m not so sure